Seismic Analysis of A 3 Dimensional High Rise Building Frame Considering Transfers Slab Using Analysis Tool Staad. Pro A Review - Karan Patel; Singhai, Ankita Singhai; Rahul Satbhaiya (International Journal of Scientific Research in Civil Engineering, 2024)
This study presented a seismic analysis of a high rise building with a transfer floor. Two structural models of high rise buildings were analyzed using static analysis method. The models were analyzed using structural software for building analysis STAAD.Pro software. The analyzed models had transfer slab system at ground floor levels in high rise building. The numerical analysis is carried out to investigate which floor system improves the global behavior of structure. For this seismic response of buildings such as bending moment and shear force were numerically evaluated. In this study, two different structural models of G+14 storey building had studied by providing a transfer slab at the bottom most storey of the building. The seismic response of high rise building such as storey shear, bending moment, displacement, axial force and torsion were numerically evaluated.
Keywords: Transfer Slab; Static Analysis; Seismic Analysis; Bending Moment; Axial Force; High-Rise Building